Study on Spatial Distribution and Heritage Corridor Network of Traditional Settlements in Ancient Huizhou - Yao Wu; Yuxin Yang; Mingrui Miao; Yonglan Wu; Hui Zhu (Buildings)
Traditional settlements are vital carriers of Chinese agricultural civilization yet face mounting challenges in protection and inheritance amid rapid urbanization. Taking ancient Huizhou as a case study, this research analyzes the spatial distribution patterns of cross-provincial traditional settlements and constructs a multi-level heritage corridor network through circuit theory modeling and space syntax analysis. The study reveals a “small aggregation, large dispersion” spatial structure shaped by natural geography and socio-cultural dynamics. Simulation of multi-path cultural flows and network analysis show that high betweenness corridors concentrate along the northeast–southwest axis, promoting efficient cultural circulation, while low betweenness areas highlight gaps in direct connectivity. Closeness analysis identifies She County as the cultural core with a single-center radial structure, though internal fragmentation persists. Based on these findings, the study proposes a “three-core-driven, two-axis linkage, multi-source synergy” protection strategy to strengthens the spatial integrity and resilience of the heritage network. This research not only provides a systematic framework for the holistic conservation of Huizhou settlement heritage but also offers methodological references for the protection of traditional settlements in broader regions.